The Network and the Society: Structure and Agency in Castells' Theory. (June 2023) - Miconi, Andrea
The aim of the article is to explore the theoretical tension between structure and agency as laid out by Manuel Castells, from The Rise of the Network Society (1996) to Networks of Outrage and Hope (2012). With agency and structure recognized as the two main axes around which general social theory rotates, Castells' work appears to be affected by discontinuity rather than continuity. The first part of his theory mainly deals with structure and with the "pre-eminence of social morphology over social action", while the second is rather based on agency, and namely on the role played by grassroots movements. I will retrace his theoretical evolution while also stressing the point that network and society are not one and the same. Therefore, any all-embracing theoretical perspective is destined to miss the target, considering that technical, political, and social affairs follow different rules and patterns.